Aestheticizing a Political Debate: Can the Creek Confederacy Be Sung Back Together? - Craig Womack (Southern Spaces, 2007)
Speaking at Emory University on April 13, 2007, Dr. Womack explores the complex historical relationship between African Americans and the Creek Confederacy through a close reading of two short stories by Creek author Alexander Posey: "Uncle Dick and Uncle Will" (1894) and "Uncle Dick's Sow" (1900).